Summary and highlights of the scientific tracks at the STI & AIDS World Congress 2013, Vienna. (May 2014) - Whale, J; Banks, J; Foley, E; Patel, R
The joint meeting of International Society for Sexually Transmitted Diseases Research (ISSTDR) and International Union against Sexually Transmitted Infections (IUSTI) was held in July 2013 in Vienna, Austria. The conference had attracted over 1300 submissions and was divided into six tracks. The track chairs reviewed all presentations and identified key themes and data that delegates should be aware of. In a conference summary session, each track chair presented these highlights. This conference report details and expands on this summary.